Tutorial on Physiology-based Pharmacokinetic (PBPK) Modeling in an Open Access Program - Marley Santos de Araújo, Jackeline; Johansson Azeredo, Francine (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objectives: To broaden the study of PBPK (Physiology-based Pharmacokinetic) modeling for Portuguese-speaking professionals and students by developing a basic simple PBPK modeling tutorial using free access software. Methods: Descriptive study for the development of a Portuguese tutorial dedicated to the use of the PK-Sim® software (version 11.2). Results: A tutorial was developed in PK-Sim®, entirely in Portuguese, which enables individuals interested in Pharmacometrics to perform a PBPK analysis in order to study and predict the pharmacokinetics of drugs based on the physiological and anatomical characteristics of a population of interest, as well as the physical and chemical properties of a specific drug. Conclusions: Considering the importance of health technologies and their subsequent assessment, this tutorial proves as a relevant tool, both for research and development and for clinical practice, as well as leveraging the democratization of the teaching and research of Pharmaceutical Sciences among Portuguese-speaking people.